Effectiveness of Board Game–Based Education in Enhancing Knowledge and Intention Toward HPV Vaccination Among Adolescent Girls - Hamka Hamka; Devita Elsanti; Dewiyanti Dewiyanti; Gst. Kade Adi Widyas Pranata; Sumarmi Sumarmi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Human papillomavirus (HPV) infection is a major cause of cervical cancer, and HPV vaccination is recommended for girls aged 11–12 years. However, HPV vaccination coverage in Indonesia remains low, partly due to limited knowledge and low intention to receive vaccination among preadolescent girls. Innovative educational strategies are needed to improve HPV vaccine acceptance. Objective: This study aimed to evaluate the effectiveness of board game–based HPV vaccine education in improving knowledge and intention to receive HPV vaccination among adolescent girls. Methods: A quasi-experimental study was conducted involving 144 girls aged 11–12 years, with 72 participants in the intervention group and 72 in the control group. The intervention group received HPV vaccine education through a board game–based approach, while the control group received conventional education. Knowledge and intention toward HPV vaccination were measured using validated questionnaires before and after the intervention. Data were analyzed using descriptive statistics, paired sample t-tests, and ANCOVA. Results: After adjustment for baseline scores and age using ANCOVA, the intervention group showed significantly higher post-test knowledge (F(1,140) = 9.65, p = 0.002, partial η² = 0.065) and intention (F(1,140) = 8.69, p = 0.004, partial η² = 0.058) compared with the control group, indicating moderate intervention effects. Conclusion: Board game–based HPV vaccine education was associated with significant improvements in knowledge and intention toward HPV vaccination among adolescent girls after controlling for baseline differences. However, these improvements were comparable to those achieved through conventional education. Interactive educational approaches may therefore serve as viable and engaging alternatives, rather than superior strategies, for supporting HPV vaccination promotion in school-based programs